Improving Vocabulary Mastery Through Contextual Teaching and Learning in MAN Padangsidimpuan - Kriswanda Krishnapatria; Zainuddin (Rahis Cendekia Indonesia, 2025)
This study investigates the effectiveness of Contextual Teaching and Learning (CTL) in improving students’ vocabulary mastery at MAN Padangsidimpuan. Vocabulary remains a major challenge for many Indonesian EFL learners, particularly when traditional methods such as memorization and translation are used. CTL offers an alternative approach by linking instructional content to real-life situations, encouraging students to construct meaning through exploration, collaboration, and authentic tasks. Using a qualitative descriptive design, data were collected through classroom observations, interviews, and documentation. The findings reveal that CTL significantly enhanced students’ understanding, retention, and practical use of vocabulary. Students demonstrated increased confidence in producing sentences, participating in discussions, and applying vocabulary in context. They also expressed that learning through real-life examples and group-based activities made vocabulary more meaningful and enjoyable. The teacher reported improved classroom engagement and noted that CTL encouraged her to design more creative and student-centered lessons. Although some challenges emerged, such as differences in learning pace and initial difficulty adapting to inquiry-based tasks, these issues gradually diminished. Overall, the study concludes that CTL is an effective and practical approach for enhancing vocabulary mastery and creating a more engaging English learning environment.